Uruguay : Fifth and Sixth Reviews Under the Stand-By Arrangement, Requests for Waiver of Nonobservance of Performance Criteria, and Financing Assurances Review; Staff Report; Staff Supplement; Staff Statement; Press Release on the Executive Board Discussion; and Statement by the Executive Director for Uruguay. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2007)
This paper discusses key findings of the Fifth and Sixth Reviews Under the Stand-By Arrangement (SBA) for Uruguay. Monetary and fiscal policies have been implemented as envisaged in the program. All quantitative performance criteria were met through end-September, except for the ceiling on public debt. In structural area, there was progress in financial sector reforms and, most importantly, the long-awaited tax reform is expected to be passed by Congress by the time of Board consideration of the reviews. However, the effort to secure tax reform delayed legislative initiatives in other areas.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet